Frailty and Upper Gastrointestinal Surgery: Initial Findings from Thailand’s First Surgical Frailty Study - Gritin Gonggetyai; Nathawadi Techalertsuwan; Chawisa Nampoolsuksan; Thammawat Parakonthun; Jirawat Swangsri; Asada Methasate; Arunotai Siriussawakul; Onuma Chaiwat; Varalak Srinonprasert (Siriraj Medical Journal, 2025)
Objective: Thailand’s aging population has led to an increase in elderly patients undergoing major surgery. Frailty is a key predictor of adverse surgical outcomes, but its impact in Thai patients remains underreported. This study aimed to determine the prevalence of frailty and its association with short-term postoperative outcomes among patients undergoing upper gastrointestinal (UGI) surgery.